2017
DOI: 10.1165/rcmb.2016-0104oc
|View full text |Cite
|
Sign up to set email alerts
|

Tensin 1 Is Essential for Myofibroblast Differentiation and Extracellular Matrix Formation

Abstract: Myofibroblasts, the primary effector cells that mediate matrix remodeling during pulmonary fibrosis, rapidly assemble an extracellular fibronectin matrix. Tensin (TNS) 1 is a key component of specialized cellular adhesions (fibrillar adhesions) that bind to extracellular fibronectin fibrils. We hypothesized that TNS1 may play a role in modulating myofibroblast-mediated matrix formation. We found that TNS1 expression is increased in fibroblastic foci from lungs with idiopathic pulmonary fibrosis. Transforming g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 49 publications
3
43
0
Order By: Relevance
“…Paxillin recruitment to FAs is mediated by vinculin, which also functions as both a structural and signaling component of the FA (Rahman et al, 2016;Subauste et al, 2004;Ziegler, Liddington, & Critchley, 2006). Tensin-1 is a structural protein within the FA which interacts with other FA proteins to mediate anchorage of actin stress fibers to each FA (Bernau et al, 2016;Zhao et al, 2016). Zyxin is reported to be the "last" protein incorporated into a mature FA and stabilizes FA-actin interaction (Zaidel-Bar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Paxillin recruitment to FAs is mediated by vinculin, which also functions as both a structural and signaling component of the FA (Rahman et al, 2016;Subauste et al, 2004;Ziegler, Liddington, & Critchley, 2006). Tensin-1 is a structural protein within the FA which interacts with other FA proteins to mediate anchorage of actin stress fibers to each FA (Bernau et al, 2016;Zhao et al, 2016). Zyxin is reported to be the "last" protein incorporated into a mature FA and stabilizes FA-actin interaction (Zaidel-Bar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hence it is likely that lower expression of TNS1 following a combined injury suggest less matrix synthesis and thus less repair potential. This is supported by the fact that TNS1 also plays an essential role in TGF‐β‐induced myofibroblast differentiation and formation of extracellular fibronectin and collagen matrix . While historically known as myocyte enhancer factor 2D, global knockout of MEF2D does not impair muscle regeneration .…”
Section: Discussionmentioning
confidence: 98%
“…Among this, some genes have been known to play a role in ligament injury, matrix organization and OA. TNS1 (tensin 1), a key component of focal adhesion, is involved in cytoskeleton organization and is required for myofibroblast differentiation and extracellular matrix (ECM) formation . Hence it is likely that lower expression of TNS1 following a combined injury suggest less matrix synthesis and thus less repair potential.…”
Section: Discussionmentioning
confidence: 99%
“…Tns1 has been shown to localize to focal adhesions and to assist in mediating signaling between the extracellular matrix and the actin cytoskeleton to impact cell movement and proliferation (35, 36). Several reports have shown that loss of Tns1 can cause a decrease in cell motility in many cell types (4648), and Tns1 has also been shown to be involved in epithelial-mesenchymal transition (EMT) of cancer cells (49). The general relationship between the expression of Tns1 and different stages/subtypes of breast cancer has been unclear.…”
Section: Discussionmentioning
confidence: 99%